2006
DOI: 10.1029/2006gc001243
|View full text |Cite
|
Sign up to set email alerts
|

Determination of temperature‐dependent stable strontium isotope (88Sr/86Sr) fractionation via bracketing standard MC‐ICP‐MS

Abstract: [1] Stable strontium isotopes (here 88 Sr/ 86 Sr) are introduced as a new member of the nontraditional stable isotopes. We have developed a bracketing standard method for the determination of d 88/86 Sr using an AXIOM MC-ICP-MS and normalizing to strontium SRM NBS987. For individual measurements the external reproducibility is better than about 25 ppm (1s RSD). For the IAPSO seawater standard a d 88/86 Sr value of 0. 381 ± 0.010% (2SEM) was determined. For the first time a temperature-dependent strontium isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
126
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 9 publications
(16 reference statements)
14
126
1
Order By: Relevance
“…We therefore propose that brachiopod samples are a reliable archive for the reconstruction of δ 88/86 Sr values of past seawater. This conforms with recent observations from cold water corals (Raddatz et al, 2013) but differs from earlier studies for warm water corals that suggested a temperature-dependent isotope fractionation in carbonates (Fietzke and Eisenhauer, 2006), implying a potential species-dependent biomineralization process analogous to that for Ca isotopes (Farkaš et al, 2007a;Gussone et al, 2005;Nägler et al, 2000).…”
Section: Sr Fractionation Factor (δ 88/86 Sr Cc-sw ) Between the Carbcontrasting
confidence: 56%
See 1 more Smart Citation
“…We therefore propose that brachiopod samples are a reliable archive for the reconstruction of δ 88/86 Sr values of past seawater. This conforms with recent observations from cold water corals (Raddatz et al, 2013) but differs from earlier studies for warm water corals that suggested a temperature-dependent isotope fractionation in carbonates (Fietzke and Eisenhauer, 2006), implying a potential species-dependent biomineralization process analogous to that for Ca isotopes (Farkaš et al, 2007a;Gussone et al, 2005;Nägler et al, 2000).…”
Section: Sr Fractionation Factor (δ 88/86 Sr Cc-sw ) Between the Carbcontrasting
confidence: 56%
“…This is due to equal 87 Sr/ 86 Sr values of seawater and its precipitates, being a consequence of neglected isotope fractionation during mass spectrometric analysis. Modeled Sr concentrations in seawater ([Sr] sw ) therefore have to rely on the less well known (Sr/Ca) sw ratios and seawater calcium concentrations ([Ca] sw ) gleaned from marine carbonates and fluid inclusions, respectively (Horita et al, 2002;Lowenstein et al, 2005;Steuber and Veizer, 2002;Wallmann, 2004 (Fietzke and Eisenhauer, 2006), are calculated using the following relation:…”
Section: Introductionmentioning
confidence: 99%
“…The stable Sr isotopic composition of some biogenic carbonates has been suggested to reflect ambient seawater temperature due to mass-dependent kinetic fractionation, in which the relative mass difference of the isotopes involved accounts for the inverse correlation to the ion mass in a kinetic fractionation process (Fietzke and Eisenhauer, 2006;Rüggeberg et al, 2008). However, more recent work has shown no relationship between seawater temperature and δ 88 / 86 Sr values from various biogenic archives Raddatz et al, 2013;Stevenson et al, 2014;Vollstaedt et al, 2014 (Krabbenhöft et al, 2010;Raddatz et al, 2013;Vollstaedt et al, 2014).…”
Section: Stable Sr Isotope Incorporation Into a Islandica And Sr Comentioning
confidence: 96%
“…If the fractionation of stable Sr isotopes in precipitated biogenic carbonates is dominated by kinetic isotope effects and not under equilibrium conditions, the δ 88 / 86 Sr ratio would likely have a strong correlation with precipitation temperature and/or precipitation rate. As an environmental proxy, 88 Sr / 86 Sr in both deep sea and tropical corals has been reported as a temperature proxy (Fietzke and Eisenhauer, 2006;Rüggeberg et al, 2008). However, more recent, higher precision work, has indicated either a null relationship (foraminifera) or negative relationship (coccolithophore) between δ 88 / 86 Sr and ambient seawater temperature, suggesting growth rate controls the uptake of Sr isotopes into biogenic carbonates Stevenson et al, 2014).…”
Section: Radiogenic Strontium Isotopes As a Water Mass Tracermentioning
confidence: 99%
See 1 more Smart Citation